THE EFFICACY OF DASHMOOLADI CHURNA IN ESSENTIAL HYPERTENSION: A CASE STUDY - Bhange, Dr. Pravin Suresh; Borakhade, Dr. Vasundhara Ramdas (International Journal of Research -GRANTHAALAYAH, 2019)
Ayurveda is one of the most ancient medical sciences of the world. It describes the basic and applied aspects of life process, health, disease and its management with the sound base of principles and approaches. 21st century is a world of industrialization & fast life which has created various life style disorders. Hypertension is one of life threatening gift of today’s life, which is psychosomatic, hereditary and occurring as a result of aging. It is also called as a silent or hidden killer because most of sufferers (85%) are asymptomatic and as per available reports, in more than 94% cases of hypertension under lying cause is not found. Such patients are said to have Essential Hypertension (EHT). Hypertension is one of the leading causes of the Global burden of disease. 60 Years male patient suffering from Anidra, Shirashoola, Bhrama, Daurbalya, Klama, Krodhaprachurya since last two months. He came to our hospital for Ayurvedic treatment. With our unique herbal combination of drug, his all symptoms got controlled. This is one single study on Dashmooladi churna to evaluate the efficiency on Essential hypertension.